Clinical Burden of Respiratory Syncytial Virus in Hospitalized Children Aged ≤5 Years (INSPIRE Study). (13th April 2022) - Hartmann, Katrin; Liese, Johannes G; Kemmling, Daniel; Prifert, Christiane; Weißbrich, Benedikt; Thilakarathne, Pushpike; Diels, Joris; Weber, Karin; Streng, Andrea
Abstract: Background: Respiratory syncytial virus (RSV) is a leading cause of hospitalizations in children (≤5 years of age); limited data compare burden by age. Methods: This single-center retrospective study included children (≤5 years of age) hospitalized for >24 hours with reverse-transcription polymerase chain reaction (RT-PCR)–confirmed RSV infection (2015–2018). Hospital length of stay (LOS), intensive care unit (ICU) admissions, ICU LOS, supplemental oxygen, and medication use were assessed. Multivariate logistic regression analyses identified predictors of hospital LOS >5 days. Results: Three hundred twelve patients had RSV infection (ages 0 to <6 months [35%], 6 to <12 months [15%], 1 to <2 years [25%], and 2–5 years [25%]); 16.3% had predefined comorbidities (excludes preterm infants). Median hospital LOS was 5.0 days and similar across age; 5.1% (16/312) were admitted to ICU (ICU LOS, 5.0 days), with those aged 0 to <6 months admitted most frequently (10/108 [9.3%]). Supplemental oxygen was administered in 57.7% of patients, with similar need across ages. Antibiotics were administered frequently during hospitalization (43.6%). Predictors of prolonged LOS included pneumonia (odds ratio [OR], 2.33), supplemental oxygen need (OR, 5.09), and preterm births (OR, 3.37). High viral load (RT-PCR RSV cycle threshold value <25) was associated with greater need for supplemental oxygen. Conclusions: RSV causes substantial burden in hospitalized children (≤5 years), particularly preterm infants and those aged <6 months.